(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to investigate in depth the communication patterns of Islamic Education teachers in learning. It is often found that the PAI learning process is not yet fully optimized; therefore, research on the communication patterns of PAI teachers is very relevant. The research method used is a qualitative approach with purposive sampling, where data is obtained from analyzing sources that have criteria for selecting research subjects. The research findings, obtained through observation, interviews, and documentation, reveal that the communication patterns of Islamic Education teachers in the learning process involve three types of communication: intrapersonal communication in the form of lesson planning, interpersonal communication in the form of learning objectives, and group communication in the form of discussions during the learning process. The structured use of these communication patterns makes the Islamic Education learning process more effective and meaningful for students.